2004
DOI: 10.1520/jfs2003432
|View full text |Cite
|
Sign up to set email alerts
|

A Minimally Destructive Technique for Sampling Dentin Powder for Mitochondrial DNA Testing

Abstract: The purpose of this paper is to present the horizontal sectioning technique used by odontologists at the Central Identification Laboratory to sample dentin for mtDNA analysis. From the perspective of DNA testing, anthropologists and odontologists at the Central Identification Laboratory work with ancient remains. In many instances, the lack of comprehensive antemortem records, the potential for fragmentation and commingling, and environmental exposure makes the use of traditional forensic identification techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The majority of ancient and forensic research using human teeth has focused on different ways to access the internal tooth tissue dentine (Alakoc and Aka, 2009;Cobb, 2002;Gilbert et al, 2003;Merriwether et al,1994;Shiroma et al, 2004), and has not considered the potential variation in mtDNA content between the different tissues and regions of the tooth (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of ancient and forensic research using human teeth has focused on different ways to access the internal tooth tissue dentine (Alakoc and Aka, 2009;Cobb, 2002;Gilbert et al, 2003;Merriwether et al,1994;Shiroma et al, 2004), and has not considered the potential variation in mtDNA content between the different tissues and regions of the tooth (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Dentine has been a preferred target as it is protected beneath a covering of enamel and cementum, a specialized calcified tissue with high cell density covering the tooth root. It is also possible to sample dentine with minimal alteration to the sample by either drilling into the pulp cavity via the root tip (Cobb, 2002), or by first removing the crown (Drancourt et al, 1998;Merriwether et al, 1994;Rudbeck et al, 2005;Shiroma et al, 2004) which can be subsequently reattached with minimal sign of alteration. In contrast, cementum has largely been ignored as a source of DNA although it also contains mineralized cells, cementoblasts and cementocytes (Bosshardt and Schroeder, 1991), located in small channels near the dentine boundary (De Leo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To access the dental DNA, many authors crushed the whole tooth (Sweet & Hildebrand, 1998;Sivagami et al, 2000;Meyer et al, 2000;Baker et al, 2001;Rubio et al, 2009), while others preferred sectioning the tooth (Gaytmenn & Sweet, 2003b;Murakami et al, 2000;Shiroma et al, 2004;PreseEki et al, 2000). The main drawback of the crushing method is that it completely destroys the teeth which is hindering further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Shiroma et al [ 27 ] demonstrated a method that allows repatriation of teeth with the body after sampling. This method involved horizontal sectioning of the teeth with subsequent sampling of the pulp and dentine via mechanical drilling from the inside of the tooth after which the two halves of tooth were waxed back together giving the appearance of an intact tooth.…”
Section: Tooth Samplingmentioning
confidence: 99%